2021
DOI: 10.1097/ccm.0000000000005044
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Policy Restricting Family Presence May Have Delayed End-of-Life Decisions for Critically Ill Patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 4 publications
0
26
0
1
Order By: Relevance
“…43,44 COVID-era visitation restrictions lengthened ICU stays and delayed decisions to limit treatments before death. 24 Therefore, supporting family presence for patients with COVID-19 is expected to improve the efficiency and quality of relationship-building between families and the medical team and preserve ICUs and their staff as critical resources.…”
Section: Common Rationales For Limiting Family Presencementioning
confidence: 99%
See 1 more Smart Citation
“…43,44 COVID-era visitation restrictions lengthened ICU stays and delayed decisions to limit treatments before death. 24 Therefore, supporting family presence for patients with COVID-19 is expected to improve the efficiency and quality of relationship-building between families and the medical team and preserve ICUs and their staff as critical resources.…”
Section: Common Rationales For Limiting Family Presencementioning
confidence: 99%
“…8,9 Although such restrictions were reasonable in the early periods of limited scientific knowledge about viral transmission, supply shortages, and rapid efforts to restructure hospitals to expand capacity, 10 reevaluation of these policies is now critical given our increased information and resources. [11][12][13] ICU visitation restrictions such as those enacted because of COVID-19 lead to incomplete grief (eg, inability to fully experience the grieving process) 11, [14][15][16][17][18] ; emotional distress experienced by patients, families, and physicians 11, [14][15][16][17][18][19][20][21][22][23] ; barriers to high-quality communication and decision-making 11, [14][15][16][17][18][19][20][21][22]24 ; perpetuation of existing inequities 11,20 ; and poor clinical outcomes. 11,14,[17][18][19][20][24][25][26] Given the serious and longlasting harm these restrictions cause for patients, family members, staff, and communities, we believe broadly prohibiting visitation of family members of patients with critical illness, including those with COVID-19, is no longer justified.…”
mentioning
confidence: 99%
“…En effet, une étude a indiqué que la restriction des visites avait retardé les conversations sur les objectifs de soins pendant la pandémie de COVID-19. 14 Parmi les conséquences les plus tragiques des restrictions des visites, citons l'incapacité des familles d'être présentes lors du décès d'un patient. Bien que la plupart des politiques incluent certaines dispositions pour les patients mourants, elles limitent toutefois le nombre de visiteurs, et les patients ou les membres de la famille soupçonnés ou confirmés COVID-19 ne peuvent en bénéficier.…”
Section: Conséquences Des Politiques De Restriction Des Visites à L'unité De Soins Intensifs Pendant La Pandémie De Covid-19unclassified
“…Indeed, one study reported that restricting visitation delayed conversations about goals of care during the COVID-19 pandemic. 14 Among the most tragic consequences of visitor restrictions is inability of the family to be present when a patient is dying. Although most policies offer some provisions for dying patients, they limit the number of visitors, and patients or family members with suspected or confirmed COVID-19 are disallowed.…”
mentioning
confidence: 99%
“…However, one study of 4,244 patients with COVID-19 in the ICU found that although 26% of patients had died at Day 28, an additional 5% died by Day 90 ( 14 ). Moreover, practices around end-of-life care and time to a decision to withdraw life-sustaining therapies may be altered by unusual circumstances such as lack of visitation by families ( 15 ). We can only speculate that using a longer-term measure such as 60- or 90-day mortality, although more difficult to measure, may reveal even less variation between hospitals.…”
mentioning
confidence: 99%